Systemic Soluble Tumor Necrosis Factor Receptors 1 and 2 Are Associated with Severity of Diabetic Retinopathy in Hispanics - Kuo, Jane Z.; Guo, Xiuqing; Klein, Ronald; Klein, Barbara E.; Cui, Jinrui; Rotter, Jerome I.; Ipp, Eli; Chen, Yii-Der Ida (Ophthalmology (Rochester, Minn.), 2012)
To investigate the associations of serum amyloid A (SAA) protein and soluble tumor necrosis factor receptors 1 and 2 (sTNF-R1 and sTNF-R2) with diabetic retinopathy (DR) in Hispanics. Prospective, nonrandomized, cross-sectional, family-based observational cohort study. A total of 473 Hispanic type II diabetic subjects in families ascertained via proband with DR. Levels of SAA, sTNF-R1, and sTNF-R2 were measured with enzyme-linked immunosorbent assay. Diabetic retinopathy was assessed by fundus photography and graded using modified Airlie House classification. Levels of SAA, sTNF-R1, and sTNF-R2 to severity of DR with and without covariates. A direct association of sTNF-R1 (2.37±0.13, 2.15±0.09, 3.09±0.24, 3.25±0.46, 5.02±0.61 ng/ml; P < 0.0001) and sTNF-R2 (6.04±0.20, 6.25±0.52, 7.96±0.70, 8.14±1.13, 14.83±1.68 ng/ml; P < 0.0001) was found for no DR, mild nonproliferative DR (NPDR), moderate NPDR, severe NPDR, and proliferative DR, respectively. These associations remained significant after adjusting for age, gender, body mass index, glycosylated hemoglobin, diabetes duration, systolic blood pressure, and serum creatinine (P < 0.0001 for sTNF-R1 and P=0.0004 for sTNF-R2). A similar pattern was observed when we adjusted for urinary albumin:creatinine ratio in place of serum creatinine (P=0.005 for sTNF-R1 and P=0.02 for sTNF-R2). Levels of sTNF-R1 and sTNF-R2 are highly correlated with the severity of DR, suggesting that inflammation and insulin resistance may play a critical role in the development of DR. These may be useful biomarkers for DR, aiding in etiologic studies and possibly identifying at-risk patients for active intervention. The author(s) have no proprietary or commercial interest in any materials discussed in this article.